Detection of chromosomal imbalances in transitional cell carcinoma of the bladder by comparative genomic hybridization. - Voorter, C. (1995)
Comparative genomic hybridization (CGH) was applied for a comprehensive screening of chromosomal aberrations in 14 transitional cell carcinomas of the bladder of different grade and stage. The results were compared in a number of selected cases with those obtained by restriction fragment length polymorphism analyses and targeted fluorescence in situ hybridization. Distinct amplifications, found with CGH, were located on 3p22-24, 10p13-14, 12q13-15, 17q22-23, 18p11, and 22q11-13. These high copy number amplifications and the frequency of imbalances involving chromosome 5, occurring in 4 of 14 cases, have not yet been identified in transitional cell carcinomas. Apart from these new aberrations, imbalances were detected in 3 or more cases for chromosomes 9 and 11, as already described previously in the literature. In four tumors, the copy number of specific chromosomal regions was also analyzed by interphase cytogenetics. Although in most instances the CGH data were confirmed, in one tumor, distinct differences were observed, possibly a result of heterogeneity of the tumor cell population. Furthermore, the CGH data were compared with loss of heterozygosity as revealed by restriction fragment length polymorphism analysis in the same tumors. In 80% of informative cases, no loss was detected by restriction fragment length polymorphism or by CGH. Of the 15 cases of loss of heterozygosity, 7 showed a loss also with CGH, whereas in 8 cases no loss was observed. In summary, CGH is a fast method to obtain a comprehensive picture of chromosomal imbalances in transitional cell carcinomas, including a number of previously unknown genomic alterations such as high level amplifications.